KORELASI GEJALA PENYAKIT FLU PADA ANAK BALITA DENGAN MENGGUNAKAN ALGORITMA SEMUT - Noni Selvia; Erlin Windia Ambarsari; Nurfidah Dwitiyanti (Pusat Riset dan Inovasi Nasional, 2022)
Influenza is one of the most common illnesses suffered by toddlers. Knowing the symptoms that appear most quickly, parents can provide appropriate first aid to their toddlers. A graph is a field of mathematics used to find the fastest pathways in a path based on the starting point to the endpoint. The graph used is a weighted graph with weights taken from the moderate pain suffered by toddlers, in which the range of a pain scale is 0 – 10. Then, using the ant algorithm to determine the distance from symptoms that often appear. The results obtained from pheromone evaporation of the ant algorithm are Fever (P1), Headache (P2), Weakness (P7), Vomiting (P8), and Diarrhea (P9). The pheromones taken as pathways were high pheromone values P1–P2 (0.0905), P2–P7 (0.0874), P7–P8 (0.0811), and P8–P9 (0.0810). Ant algorithm can identify flu symptoms in children under five and explain the relationship between the symptoms.